The impact of green economy on sustainable development in the Jordanian Islamic bank environment - Omar M. Alhawtmeh; Eman Mohammed Al-Nimr; Thikra Alqmool (Heritage and Sustainable Development)
The study aimed to demonstrate the impact of the green economy on sustainable development in Jordanian Islamic banks, and to identify the advantages, characteristics and concepts of transitioning to the green economy and its relationship in Jordanian Islamic banks also the study aim to clarify the importance of the banking system supporting the green economy by providing the necessary financing and its effective role as a major financial intermediary between investors and savers, in addition to developing a strategy to enable the transition to the green economy and full support for green projects in the coming years and maintaining sustainable development of Islamic banks environment. The descriptive analytical approach was used, 160 questionnaires were distributed, 149 were retrieved valid for statistical analysis, and the data were analyzed by the SPSS program. The results showed a significant impact of the green economy on sustainable development in its dimensions (environmental development, social development, and economic development) in Jordanian Islamic banks. The study recommended the need to develop comprehensive strategies for transitioning to the green economy shared in all sectors and programs and to adhere to Sharia and ethical controls in all Islamic financing operations in order to reduce economic and environmental risks